As representações sobre/do patrimônio arquitetônico da Comissão Telegráfica de Rondon em Mato Grosso - Waldow, Priscila (2018)
This dissertation aims to analyse the architetural patrimony remainder of the Telegraphic Commission action period, led by Marechal Rondon in the XX century in Mato Grosso. Five buldings composes as analyzes: Coronel Generoso Ponce’s in the Capim Branco Comunity at Campo Verde town; Telegraphic Station of Porto Esperidião; Telegraphic Station of Pontes e Lacerda; Gas Station in Porto of Tapirapoan, nowadays Settlement Antônio Conselheiro in Tangará da Serra and Telegraphic Station of Affonso in the city of Santo Afonso. In order to understand structure safeguard in the historic patrimony in Mato Grosso, the analyzes start from historical trajectory of patrimonial policies in Brazil, and how the processes for valuation the cultural assets of the state. We return to the comprehension about the history concepts in its interelations with the achitecture, how sciences that are complemented in the analyzes of the material patrimony, presenting in this research the architectural surveys expressed in the graphical representations of telegraphic stations nowadays, which serve as the basis for technical-constructive inquiries, compared with historical records, contained in the reports and other documents of Telegraphic Commission, in order to understand the changes that the buildings sufer long in more than a century of existence, and in the way that political actions of the State Government intervened in this process. We used in the research the methodology of patrimonial education as basis for critical reflection of the valuation procedures of historial patrimony in the current scenario, in the nonobservance of contínuos actions, that comprehends the educatives activities proposes, as a tool for generate knowledge and sense of belonging to individual to heritage. The discussions pass run historical trajectory of public policies for the protection of assets in Mato Grosso and the impact of the actions in favor of the commemorations of the Centenary of the Rondon Commission, which began in 2007 and which allocated resources for the works in four of the five buildings analyzed , and that unfold in other initiatives of the State Secretariat of Culture for the valorization of the history of Rondon in Mato Grosso.